2021
DOI: 10.21037/tcr-20-3125
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to lymphocyte and platelet to lymphocyte ratios as biomarkers to predict relapse and survival in posthepatectomy HBV-related hepatocellular carcinoma: a meta-analysis and preliminary immune perspective

Abstract: Background: Hepatitis B virus (HBV) infection represents the major etiology of hepatocellular carcinoma (HCC) and results in poor outcomes. Accumulating evidence suggests that composite immune cell-based biomarkers such as neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) have prognostic value in postoperative HCC patients. However, due to the complexity, differential etiology, and the presence of variable confounding factors in different studies, the relationship between these marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Our study showed that CA199 was positively correlated with the NLR, PLR, and CRP but negatively correlated with the LMR and AAPR in CCA patients, so CA19-9 was correlated with markers of the systemic inflammatory response. High NLR, PLR, and CRP and low LMR and AARP were associated with advanced clinicopathological features and poor prognosis [ 5 – 7 ], which can be concluded that high levels of CA19-9 are associated with poor prognosis of CCA. At the same time, it was found in our study that CA19-9 was negatively correlated with the B/K ratio.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study showed that CA199 was positively correlated with the NLR, PLR, and CRP but negatively correlated with the LMR and AAPR in CCA patients, so CA19-9 was correlated with markers of the systemic inflammatory response. High NLR, PLR, and CRP and low LMR and AARP were associated with advanced clinicopathological features and poor prognosis [ 5 – 7 ], which can be concluded that high levels of CA19-9 are associated with poor prognosis of CCA. At the same time, it was found in our study that CA19-9 was negatively correlated with the B/K ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is one of the hallmarks of cancer, and the pro-inflammatory effects of markers of systemic inflammatory response (SIR) that often reflect cancer immune status, such as plasma C-reactive protein (CRP), platelet to lymphocyte ratio (PLR), neutrophil to lymphocyte ratio (NLR), and lymphocyte to monocyte ratio (LMR), have been shown to play an important role in the development and progression of cancer. SIR is also a potential prognostic and/or predictive factor for hepatocellular carcinoma, colorectal cancer, and other malignancies [ 5 ]. The albumin-to-alkaline-phosphatase ratio (AAPR) is an index based on serum biomarkers, which may not only reflect the liver functional reserve but also be associated with inflammation and cancer cell proliferation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBV-HCC prognosis is linked to several factors, including tumor burden, AFP, disease stage, ALBI, and NLR (18,19), and there are also nomograms about HBV-HCC (20)(21)(22). However, no nomogram for HCC patients with high HBsAg expression after local treatment has been available to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…At present, most of the studies on biomarkers related to the prediction of HCC targeted therapy are still in the preliminary stage, and more large samples and prospective clinical studies are needed to verify them. Currently, some studies have successively reported various substances or cells as biomarkers for predicting the prognosis of patients with HCC after liver resection ( 16 , 17 ), but there are few biomarkers that predict the efficacy of lenvatinib. In a random phase III non-inferiority trial (REFLECT), there was a trend that lower VEGF, angiogenin-2 (Ang-2), and FGF21 serum levels at baseline were associated with better outcomes with lenvatinib; early changes in rehabilitation and treatment of contaminated Soil in the treatment of HCC, Ang-2 levels, AFP response, baseline albumin bilirubin (ALBI) score, change in the ALBI score, neutrophil to lymphocyte and platelet to lymphocyte ratios were early predictors of objective response (OR) in patients with HCC undergoing lenvatinib treatment ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%